MANAGEMENT OF PHALANGEAL FRACTURES OF HAND - Ahmad, Muhammad; Hussain, Syed Shahid; Rafiq, Zulqarnain; Tariq, Farhan; Khan, M. Ibrahim; Malik, Saleem A. (Journal of Ayub Medical College Abbottabad, 2006)
Background: Phalangeal fractures are approximately 10% of all the fractures of skeletal system. Most fractures are functionally stable. Surgical treatment is necessary when fracture is displaced and reduction is not possible. This study was conducted in order to study the aetiology, features and management of the phalangeal fractures of hand. Methods : This descriptive study was conducted in the department of Plastic Surgery, Pakistan Institute of medical Sciences, Islamabad from June 1st 2002 to July 31st 2003. Adult patients of either sex with acute injury presenting in the out-patient department and emergency department were included whereas patients below the age of 13 years and patients with amputated digits were excluded. The site and side of fracture were noted. All patients were X-rayed pre-operatively. These patients were divided into two groups. Group A comprised of those patients in whom only closed reduction was done. Group B comprised of patients in whom operative procedure was carried out. Various modalities used were percutaneous Kirschner wire fixation, open reduction and internal fixation with K-wires, screws, microplates and dental wires/ after operation, immobilization of fracture site was done for 3 - 4 weeks. Chi square test was used for statistical analysis of complications in both the groups. Results: 51 fractures were seen in 43 men and 8 fractures in 8 females. Mean age of the patients of group A was 35.6 years as compared to 29.5 years of group B. 31% fractures were associated with soft tissue injury. Ring finger was the commonest to be involved in 36% patients. Left hand (64%) was commonly involved. Left proximal phalanx (31%) was the most frequently injured part. Intraarticular fractures were seen in 10% cases. 15 fractures were treated conservatively and some kind of operative modality was used in 44 fractures. Crush injury remained the commonest cause. In 36% patients fractures were fixed with K-wire using open reduction and internal fixation technique. In 22% patients, only percutaneous K-wire was used. In two patients, dynamic traction device was used. One case of post operative infection was noticed in group B. Whereas only one case of malunion and one case of limited joint movement and stiffness was noted in group A. Conclusions: Results of both the closed reduction and open reduction and internal fixation were equally good (p < 0.05). If there is any soft tissue injury, it is advisable to use open reduction and internal fixation technique. Keywords : Phalangeal fracture, Open reduction, Internal fixation, K-wire